A Population Approach to Characterize Interferon Beta‐1b Effect on Contrast Enhancing Lesions in Patients With Relapsing Remitting Multiple Sclerosis. (24th April 2015) - Gulati, A; Bagnato, F; Villoslada, P; Velez de Mendizabal, N
<x xml:space="preserve">Abstract</x> In patients with relapsing‐remitting multiple sclerosis (RRMS), interferon beta‐1b (IFNβ‐1b) reduces the occurrence of contrast enhancing lesions (CELs) on magnetic resonance imaging (MRI). Questions remain on the stability of IFNβ‐1b effect over time and its action beyond the reduction of CELs. In this study, we described the IFNβ‐1b effect by a mixed effects model, quantifying the interpatient variability associated with its parameters. Using a negative binomial distribution model as a natural history model, the effect of IFNβ‐1b was evaluated using different mathematical functions of time. IFNβ‐1b produced a decrease in the expected CEL numbers, inhibiting the formation of new CELs but did not promote the resolution of the already‐formed ones. Based on the final selected model, simulations were carried out to optimize the combined IFNβ‐1b‐corticosteroid therapy as a proof‐of‐concept. In summary, we provide evidence on the dynamics of CELs under IFNβ‐1b treatment that can be used to monitor the effects of therapies in MS.